2008
DOI: 10.1007/s10340-008-0219-8
|View full text |Cite
|
Sign up to set email alerts
|

Calling behaviour and male response towards sex pheromone of poplar moth Condylorrhiza vestigialis (Lepidoptera: Crambidae)

Abstract: The calling behaviour of virgin females Condylorrhiza vestigialis Guenée, 1854 (Lepidoptera: Crambidae) and the female pheromone gland extract activity were studied under laboratory conditions. Most of the females started calling from their Wrst scotophase period after emergence. Maximum calling occurred between the seventh and tenth hours of the scotophase period. The length of the calling increased with age until the fourth scotophase, but the onset of calling time did not diVer with age. The number of calli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Large females produce more attractive blends of sex pheromone than small females and males preferentially select and mate with large females (Jaffe et al, 2007;Xu & Wang, 2009;Harari et al, 2011). Results of the present study further emphasize the significance of body weight in determining mating success, since calling over prolonged periods may enhance the probability of females mating when competing for males (Ambrogi et al, 2009). A positive correlation between body weight and pheromone release is also reported (Huang et al, 1992).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Large females produce more attractive blends of sex pheromone than small females and males preferentially select and mate with large females (Jaffe et al, 2007;Xu & Wang, 2009;Harari et al, 2011). Results of the present study further emphasize the significance of body weight in determining mating success, since calling over prolonged periods may enhance the probability of females mating when competing for males (Ambrogi et al, 2009). A positive correlation between body weight and pheromone release is also reported (Huang et al, 1992).…”
Section: Discussionsupporting
confidence: 77%
“…Calling behaviour, in which females release sex pheromones to attract males, is a prerequisite for mating in moths. Many studies have shown that calling is affected by endogenous and exogenous factors, including temperature (Mozuraitis & Buda, 2006), photoperiod (Gomez & Rojas, 2006), age (Ambrogi et al, 2009), mating status (McNamara et al, 2009), presence of host or non-host plant leaves (Sadek & Anderson, 2007) and perception of the pheromone produced by conspecifics (Lim et al, 2007). Nevertheless, the effect of body weight on calling behaviour has rarely been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In most taxa, males perform the majority of mate searching (Barnes 1982;Kasumovic and Andrade 2004;Kasumovic et al 2007;Ambrogi et al 2008), and females are more likely than males to encounter more mates than required for optimal fitness (Kokko and Wong 2007). Encountering too many mates can be costly rather than merely superfluous (Arnqvist and Nilsson 2000;Kawagoe et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Although finding a mate is paramount for all sexually reproducing organisms, effort spent searching for a mate is often markedly different between the sexes (Barnes 1982;Kasumovic and Andrade 2004;Kasumovic et al 2007;Ambrogi et al 2008). In most taxa, males perform the majority of mate searching (Barnes 1982;Kasumovic and Andrade 2004;Kasumovic et al 2007;Ambrogi et al 2008), and females are more likely than males to encounter more mates than required for optimal fitness (Kokko and Wong 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The same methodology was used for a 12-h photo-scotophase aeration collection. Volatiles were eluted from Super Q with 4 mL of distilled hexane and concentrated to 600 μL (1 insect per 2 μL) under an argon stream (Ambrogi et al 2009), and 1 μL was injected in a GC-MS system (QP-2010 Plus, Shimadzu).…”
mentioning
confidence: 99%